Duration of sedation effects on the ACTH stimulation test in healthy dogs - Jake Salzman; Shelly Olin; Alejandro Esteller-Vico; Luca Giori (PLoS ONE, 2025)
Background Sedation is frequently required in dogs for diagnostic workups and patient safety. Yet, sedation affects serum cortisol levels; butorphanol elevates cortisol, while dexmedetomidine reduces it dose dependently. Understanding the duration of sedation’s impact on cortisol concentration is important. Hypothesis/objectives To evaluate serum cortisol at time 0 and 6-hours post-administration of intravenous (IV) saline (0.5 mL), butorphanol (0.3 mg/kg) and combination of butorphanol and dexmedetomidine (0.3 mg/kg and 5 µg/kg, respectively). Additionally, to compare post-adrenocorticotrophic hormone (ACTH) cortisol concentration at 7 hours after these treatment protocols. Animals 12 healthy, castrated, colony beagles Methods Randomized, controlled, repeated-measure crossover design with a one-week washout between treatments. Serum cortisol was measured at time 0 (T0) and 6-hours (T6) post-IV administration of saline (0.5 mL), butorphanol (0.3 mg/kg), or combination butorphanol and dexmedetomidine (0.3 mg/kg and 5 µg/kg, respectively). An ACTH-stimulation test was performed at 6-hours post-treatments. Cortisol concentrations were compared with a mixed model analysis with treatment and time as fixed factors. Results Mean (± standard deviation) serum cortisol concentration was not significantly different at T0 and T6 following saline (T0 1.47 ± 1.12; T6 0.91 ± 0.29 µg/dL) butorphanol (0.9 ± 0.41; 0.95 ± 0.38 µg/dL) and combination butorphanol and dexmedetomidine (0.96 ± 0.43; 1.62 ± 0.9 µg/dL) (p = 0.29). There was no significant difference in post-ACTH cortisol for saline, butorphanol, or combination treatment (8 ± 2.25; 8.66 ± 2.26; 8.46 ± 1.83 µg/dL, respectively; p = 0.84) Conclusions and clinical importance In healthy dogs following treatment with the aforementioned protocols, cortisol concentration returns to baseline by 6 hours. An ACTH stimulation test started 6-hours post-treatment is not affected by these drug protocols. Additional studies are needed in dogs with adrenal dysfunction.